Spectrum and States of the BCS Hamiltonian in a Finite Domain. II. Spectra of Excitations - Petrina, D. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We establish that the averages per volume of the BCS and approximating Hamiltonians over all excited states coincide in the thermodynamic limit. Earlier, this was established only for the ground state.